Elaboración de un manual de calidad para la rectificación de motores de vehículos en la rectificadora Figueroa ubicada en la ciudad de Latacunga. - Lema Sasi, Luis David (2021)
The present titling work consists of making a quality manual for the rectification of vehicle engines in the "RECTIFIACDORA FIGUEROA" located in the city of Latacunga, province of Cotopaxi. For the development of the investigation, bases were taken of what is a rectification of an engine as well as quality references that can be used in the elaboration of this quality manual. Initially, an internal audit was carried out to determine the current status of the company with respect to the rectification procedures, said audit consists of the analysis of each activity carried out by the operator from the reception of the area to be rectified until it is finished and delivered. to the client. As results of the initial audit, it was obtained that the operators do not follow a specific process in the rectification of an engine and that the less difficult works are carried out immediately, leaving behind the other rectification works. This leads to operators taking longer to deliver the first rectification jobs requested and leaving the customer dissatisfied and upset at the time of delivery. Causing the client to take other alternatives for the requested work and not return. Therefore, there is the initiative to develop the quality manual for rectifying vehicle engines with the objective of customer satisfaction and enhancement of the company.